Publishing Agreement - ANJS (Al-Nahrain Journal of Science, 2018)
This is an agreement under which all authors (represented by the corresponding author) of the article grant license to publish your article (titled in this document) including abstract, data, tables and figures and their explanation and the supplemental materials (if provided) in Al-Nahrain Journal of Science. This agreement is valid for the full period of copyright throughout the world and the right to publication is granted in all forms, formats and in all media of this time and in the future. This agreement includes that all the authors comply with the Journal’s policies on peer-review and publishing ethics. This agreement must be read, understood and agreed to the terms and conditions of this agreement.